Sistem Monitoring Penggunaan Beban Pada Proses Pengosongan Baterai 100WP Menggunakan Sensor PZEM-004T - andari, rafika (UNIB Press, 2021)
In this study, a prototype tool of plts battery discharge monitoring system was created that aims to facilitate in monitoring plts system, solar panel battery usage monitoring system equipped with arduino microcontroller, current sensor, voltage and power that has been calibrated, so that the data acquisition system integrated in arduino microcontroller based system can be obtained in real time. From the results of the study, according to the microcontroller planner used in this final task is arduino UNO328 and sensor PZEM-004T. This monitoring tool is capable of reading voltage, current, power, cosphi and battery capacity in percent at the time of load supply.